ERO modelling of net and gross erosion of marker samples exposed to L-mode plasmas on ASDEX Upgrade. (December 2020) - Hakola, A.; Keitaanranta, A.; Kumpulainen, H.; Lahtinen, A.; Likonen, J.; Balden, M.; Cavedon, M.; Krieger, K.; Airila, M.; Groth, M.; ,; ,
Highlights: Gross and net erosion studied in ASDEX Upgrade using Au and Mo marker coatings. Largest erosion at the strike point and re-deposition small outside of the markers. Based on ERO simulations, electron temperature has the largest impact on erosion. A faint toroidal tail of re-deposited particles predicted downstream of the markers. Re-deposition drops from >50% to <40% with marker size decreasing from 5 mm to 1 mm. Abstract: In this paper, we report experimental and numerical investigations of gross and net erosion of gold (Au) and molybdenum (Mo), proxies for the common plasma-facing material tungsten (W), during L-mode plasma discharges in deuterium (D) in the outer strike-point region of the ASDEX Upgrade tokamak. To this end, erosion profiles of different marker spots (for Au, dimensions 1 × 1 and 5 × 5 mm 2 ) and marker coatings (for Mo) have been determined and modelled using the ERO code. The smaller marker spots were designed to quantify the gross-erosion rate while on the bigger markers local prompt re-deposition of Au allowed obtaining data on net erosion. The experimental results indicate relatively uniform erosion profiles across the marker spots or coatings, very little re-deposition elsewhere, and the largest erosion taking place close to the strike point. Compared to W, the markers show up to 15 times higher net erosion but no major differences in the poloidal migration lengths of Au and W can be seen. Gold thus appears to be a proper choice for studying migration of W in the divertor region. The ERO simulations with different background plasmas are able to reproduce the main features of the experimental net erosion profile of Au. Of the studied parameters, electron temperature has the strongest impact on erosion: doubling the temperature enhances erosion by a factor of 2.5–3. In contrast, for Mo, the simulated net erosion is 3 times smaller than what experimental data indicate. The discrepancies can be attributed to the deviations of the background plasma profiles from the measured ones as well as to the applied models or approximations for the ion temperature, plasma potential, and sheath characteristics in ERO. In addition, the surrounding areas of the marker samples being covered with impurities and W from previous experiments may have considerably reduced the actual re-deposition of Mo. All the simulations predict a toroidal tail of re-deposited particles, downstream of the markers, but the particle density seems to be below the experimental detection threshold. The comparison between the 1 × 1 mm 2 and 5 × 5 mm 2 marker spots further reveal that re-deposition drops from >50% to <40% when decreasing the marker size. This indicates that small enough marker samples can be used for accurately determining gross erosion in ASDEX Upgrade.